Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

Hydramethylnon induces synergistic toxicity of pyrethroid mixtures in human lung epithelial cells - Hye-Jin Jeong; Hye-In Park; Tae-Rim Im; Ju-Hui Im; Seung Min Choi; Chang-Ik Choi; Myungwon Seo; Yong Joo Park (Toxicological Research, 2026)

Interaction between ethanol and flunitrazepam in rats: Pharmacokinetic mechanisms and toxicological implications - Yejin Kim; Jeong In Seo; Jin Ah Won; Sooyeun Lee; Hye Hyun Yoo (Chemico-Biological Interactions, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Hydramethylnon-induced autophagy and apoptosis in human bronchial epithelial cells by homeostatic changes - Yeon-Ho Kang; Sou Hyun Kim; Hye-Jin Jeong; Ah-Yoon Song; Hye-In Park; Eun-Hye Kim; Young-Suk Jung; Yong Joo Park (Toxicology, 2026)

Molecular biomarkers associated with environmental naphthalene exposure in the respiratory system - Hye-Jeong Han; Amartuvshin Baasankhuu; Bogun Kim; Angela Astrid Sekar Prameswari; Karina Kalani; Paolo Panza; Sangwoo Lee; Woo-Keun Kim; In-Geol Choi; Cheol-Hee Kim; Hyun-Taek Kim (Science of The Total Environment, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Seasonal and spatial distributions of polycyclic aromatic hydrocarbons in surface water of the Taehwa River in the largest industrial city in South Korea - In-Gyu Cho; Hye-Ok Kwon; Sung-Hee Seo; Joo-Yeon Oh; Eun-Jeong Park; Sung-Deuk Choi (Environmental Monitoring and Assessment, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Seasonal dynamics of picocyanobacteria and bloom-forming cyanobacteria in Daechung Reservoir, Korea - Hye Jeong Choi; In-Chan Choi; So Hyun Cho; Eun-mi Hong; Jay Jung Lee (Paddy and Water Environment, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Integrative assessment of mixture toxicity of household chemicals using the toxic unit approach and mode of action - Hye-Jin Jeong; Yeon-Ho Kang; Ah-Yoon Song; Hye-In Park; Myungwon Seo; Yong Joo Park (Toxicology, 2025)

Development of a comprehensive air risk index and its application to high spatial-temporal health risk assessment in a large industrial city - Sang-Jin Lee; In-Gyu Cho; Ho-Young Lee; Jeong-Tae Ju; Hye-Jung Shin; Sung-Deuk Choi (Environmental Pollution, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Conjugated polymer of Multi-arm-PEG and dimethylsiloxane (CPMD) for the effective transdermal delivery of deoxycholic acid for fat reduction - Hwajun Jeong; Hye-Lin Kim; Harim Kim; Min-Suk Lee; Jae-Min Cho; Chan Lee Park; Hyo In Kim; Jinbong Park; Dokyoung Kim (Chemical Engineering Journal, 2025)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

Morphology and molecular phylogeny of Euplotes baugilensis n. sp. (Ciliophora, Spirotrichea), with an illustrated key to Euplotes species with reduced cirri - Eun-Hye Do; Hye-In Kwon; Jeong Hyeon Yeo; Pablo Quintela-Alonso; Jae-Ho Jung (European Journal of Protistology, 2024)

Exploring pharmacokinetics and herb-drug interactions of an herbal extract mixture derived from Poria cocos and Morus alba L. - So Yeong Yun; Jeong In Seo; Sang Zin Choi; Ja Young Ryu; Ah Yeon Park; Han Gon Choi; Hye Hyun Yoo (Journal of Pharmaceutical Investigation, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Evaluating flavonoids as potential aromatase inhibitors for breast cancer treatment: In vitro studies and in silico predictions - Jeong In Seo; Jun Sang Yu; Yonghui Zhang; Hye Hyun Yoo (Chemico-Biological Interactions, 2024)

Combination approach of paired starter culture and lactic acid on inhibiting autochthonous lactic acid bacteria for extending kimchi shelf life - Chang Hee Jeong; Hye In Ko; Mo Eun Lee; Sung-Gi Min; Mi-Ai Lee; Tae-Woon Kim (Food Control, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

Maternal PM2.5 exposure is associated with preterm birth and gestational diabetes mellitus, and mitochondrial OXPHOS dysfunction in cord blood - Young-Ah You; Sunwha Park; Eunjin Kwon; Ye-Ah Kim; Young Min Hur; Ga In Lee; Soo Min Kim; Jeong Min Song; Man S. Kim; Young Ju Kim; Young-Han Kim; Sung Hun Na; et al. (Environmental Science and Pollution Research, 2024)
Maternal exposure to fine particulate matter (PM 2.5 ) is associated with adverse pregnancy and neonatal health outcomes. To explore the mechanism, we performed mRNA sequencing of neonatal cord blood. From an ongoing prospective cohort, Air Pollution on Pregnancy Outcome (APPO) study, 454 pregnant women from six centers between January 2021 and June 2022 were recruited. Individual PM 2.5 exposure was calculated using a time-weighted average model. In the APPO study, age-matched cord blood samples from the High PM 2.5 (˃15 ug/m 3 ; n = 10) and Low PM 2.5 (≤ 15 ug/m 3 ; n = 30) groups were randomly selected for mRNA sequencing. After selecting genes with differential expression in the two groups ( p -value < 0.05 and log2 fold change > 1.5), pathway enrichment analysis was performed, and the mitochondrial pathway was analyzed using MitoCarta3.0. The risk of preterm birth (PTB) increased with every 5 µg/m 3 increase of PM 2.5 in the second trimester (odds ratio 1.391, p = 0.019) after adjusting for confounding variables. The risk of gestational diabetes mellitus (GDM) increased in the second (odds ratio 1.238, p = 0.041) and third trimester (odds ratio 1.290, p = 0.029), and entire pregnancy (odds ratio 1.295, p = 0.029). The mRNA-sequencing of cord blood showed that genes related to mitochondrial activity (FAM210B, KRT1, FOXO4, TRIM58, and FBXO7) and PTB-related genes (ADIPOR1, YBX1, OPTN, NFkB1, HBG2) were upregulated in the High PM 2.5 group. In addition, exposure to high PM 2.5 affected mitochondrial oxidative phosphorylation (OXPHOS) and proteins in the electron transport chain, a subunit of OXPHOS. These results suggest that exposure to high PM 2.5 during pregnancy may increase the risk of PTB and GDM, and dysregulate PTB-related genes. Alterations in mitochondrial OXPHOS by high PM 2.5 exposure may occur not only in preterm infants but also in normal newborns. Further studies with larger sample sizes are required.

Effect of pulsed electric field pretreatment on mass transfer during hot air drying: Drying and rehydration properties of sweet potato - Si-Yoen Kim; Ui-Chan Jeong; Hye-In Ju; Seho Jeong; Dong-Un Lee (Innovative Food Science & Emerging Technologies, 2023)

Mechanisms of interactions in pattern-recognition of common glycostructures across pectin-derived heteropolysaccharides by Toll-like receptor 4 - Gyu Hwan Hyun; In Ho Cho; Yoon Young Yang; Da-Hye Jeong; Yun Pyo Kang; You-Sun Kim; Seul Ji Lee; Sung Won Kwon (Carbohydrate Polymers, 2023)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Land use types with different fertilization management affected isotope ratios of bulk and water-extractable C and N of soils in an intensive agricultural area - Young-Jae Jeong; Hyun-Jin Park; Byeong-Jun Jeon; Bo-Seong Seo; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2022)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

T cell receptor repertoires of ex vivo–expanded tumor-infiltrating lymphocytes from breast cancer patients - In Ah Park; Hajar Rajaei; Young-Ae Kim; Hyeonjin Lee; Heejae Lee; Jeong-Han Seo; Sun-Hee Heo; In Hye Song; Gyungyub Gong; Hee Jin Lee (Immunologic Research, 2020)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Impact of soil moisture initialization on boreal summer subseasonal forecasts: mid-latitude surface air temperature and heat wave events - Eunkyo Seo; Myong-In Lee; Jee-Hoon Jeong; Randal D. Koster; Siegfried D. Schubert; Hye-Mi Kim; Daehyun Kim; Hyun-Suk Kang; Hyun-Kyung Kim; Craig MacLachlan; Adam A. Scaife (Climate Dynamics, 2019)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Individualized metabolic profiling stratifies pancreatic and biliary tract cancer: a useful tool for innovative screening programs and predictive strategies in healthcare - Jun Hwa Lee; Seung Eun Yu; Kyung-Hee Kim; Myung Hyun Yu; In-Hye Jeong; Jae Youl Cho; Sang-Jae Park; Woo Jin Lee; Sung-Sik Han; Tae Hyun Kim; Eun Kyung Hong; Sang Myung Woo; et al. (EPMA Journal, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Genetic variability comparison of cultured Israeli carp (Cyprinus carpio) from Korea using microsatellites - Jung Eun Kim; In Bon Goo; Ju-ae Hwang; Hyeong Su Kim; Hye-Sung Choi; Jeong-Ho Lee (Genes & Genomics, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

A new method to classify ENSO events into eastern and central Pacific types - Hye‐In Jeong; Joong‐Bae Ahn (International Journal of Climatology, 2017)
In order to clearly classify El Niño–Southern Oscillation ( ENSO ) events into eastern Pacific ( EP ) and central Pacific ( CP ) types, we develop two new indices defined as pattern correlation coefficients ( PCCs ) between monthly sea surface temperature ( SST ) anomalies ( SSTAs ) and first two leading empirical orthogonal function modes of tropical Pacific (20°S–20°N, 110°E–70°W) SSTAs . These new indices not only show close relationships with ENSO indices derived from several previous methods, but also demonstrate reasonable abilities to distinguish between two types of ENSO event. The major characteristic features of the EP ‐type and CP ‐type ENSO forcings are well captured from SST responses regressed onto each new index. Furthermore, the monthly frequencies of occurrences derived from two indices are quite similar to variation patterns of phase‐locking behaviours of two types of ENSO event.

Sound wave affects the expression of ethylene biosynthesis-related genes through control of transcription factors RIN and HB-1 - Joo Yeol Kim; Hye Ryun Ahn; Sun Tae Kim; Cheol Woo Min; Soo In Lee; Jin A. Kim; Soo-Chul Park; Mi-Jeong Jeong (Plant Biotechnology Reports, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Analysis of an ECG Record Database Reveals QT Interval Prolongation Potential of Famotidine in a Large Korean Population - Jaesuk Yun; Eun Hwangbo; Jongpill Lee; Chong-Run Chon; Peol A. Kim; In-Hye Jeong; Manyoung Park; Raewoong Park; Shin-Jung Kang; Donwoong Choi (Cardiovascular Toxicology, 2015)

Interdecadal change of interannual variability and predictability of two types of ENSO - Hye-In Jeong; Joong-Bae Ahn; June-Yi Lee; Andrea Alessandri; Harry H. Hendon (Climate Dynamics, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Isolation and characterization of polymorphic microsatellite markers from the Korean common squid Todarodes pacificus (Ommastrephidae) - Hye Suck An; Eun Mi Kim; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Genetic diversity and differentiation of the Korean starry flounder (Platichthys stellatus) between and within cultured stocks and wild populations inferred from microsatellite DNA analysis - Hye Suck An; Myung Mo Nam; Jeong In Myeong; Chul Min An (Molecular Biology Reports, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Genetic differences between broodstock and offspring of seven-band grouper in a hatchery - Hye Suck An; Jae Kwon Cho; Kyong Min Kim; Maeng Hyun Son; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Isolation and characterization of 26 novel polynucleotide microsatellites from short barbeled grunter (Hapalogenys nitens) for genetic analysis - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Conservation Genetics Resources, 2014)

Characterization of 22 polymorphic microsatellite markers for seven-band grouper Epinephelus septemfasciatus developed using a 454 pyrosequencing approach - Hye Suck An; Jae Kwon Cho; Kyong Min Kim; Maeng Hyun Son; Jeong In Myeong; Chul Min An (Conservation Genetics Resources, 2014)

Population genetic structure of the tongue sole (Cynoglossus semilaevis) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Hee Woong Kang; Hyon Sob Han; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Development of freshwater sediment management standards for organic matters, nutrients, and metals in Korea - In Ae Huh; Yong Seok Kim; Soon Ju Yu; Stella Wong; Won Sik Shin; Hye Ok Park; Ho Jeong Kim; Hyun Woo Kim (Environmental Science and Pollution Research, 2014)

Comparative genetic diversity of wild and hatchery-produced Pacific oyster (Crassostrea gigas) populations in Korea using multiplex PCR assays with nine polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Woo Jin Kim; Hyun Jeong Lim; Eun Mi Kim; Soon Gyu Byun; Young Baek Hur; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Genetic differences between wild and hatchery populations of red sea cucumber (Stichopus japonicus) inferred from microsatellite markers: implications for production and stocking programs design - Hye Suck An; Jang Wook Lee; Seong Wan Hong; Ha Neui Hong; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Assessment of the APCC coupled MME suite in predicting the distinctive climate impacts of two flavors of ENSO during boreal winter - Hye-In Jeong; Doo Young Lee; Karumuri Ashok; Joong-Bae Ahn; June-Yi Lee; Jing-Jia Luo; Jae-Kyung E. Schemm; Harry H. Hendon; Karl Braganza; Yoo-Geun Ham (Climate Dynamics, 2012)

Clinical and genetic factors affecting tacrolimus trough levels and drug-related outcomes in Korean kidney transplant recipients - In-Wha Kim; Yoo Jin Moon; Eunhee Ji; Kyung Im Kim; Nayoung Han; Sung Ju Kim; Wan Gyoon Shin; Jongwon Ha; Jeong-Hyun Yoon; Hye Suk Lee; Jung Mi Oh (European Journal of Clinical Pharmacology, 2012)

CYP2C9*3 and *13 alleles significantly affect the pharmacokinetics of irbesartan in healthy Korean subjects - Chang-Ik Choi; Mi-Jeong Kim; Eun-Kyung Chung; Hye-In Lee; Choon-Gon Jang; Jung-Woo Bae; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2012)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

An improved method of protein isolation and proteome analysis with Saccharina japonica (Laminariales) incubated under different pH conditions - Eun-Young Kim; Dong-Gyun Kim; Yu-Ri Kim; Hye-Jung Hwang; Taek-Jeong Nam; In-Soo Kong (Journal of Applied Phycology, 2011)

Isolation and characterization of a Glutamate decarboxylase (GAD) gene and their differential expression in response to abiotic stresses from Panax ginseng C. A. Meyer - Jung-Hye Lee; Yu-Jin Kim; Dae-Young Jeong; Gayathri Sathiyaraj; Rama Krishna Pulla; Ju-Sun Shim; Jun-Gyo In; Deok-Chun Yang (Molecular Biology Reports, 2010)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)